Spatial attention can modulate audiovisual integration at multiple cortical and subcortical sites - Fairhall, S. L.; Macaluso, E. (The European journal of neuroscience, 2009)
The role of attention in multisensory integration (MI) is presently uncertain, with some studies supporting an automatic, pre‐attentive process and others suggesting possible modulation through selective attention. The goal of this functional magnetic resonance imaging study was to investigate the role of spatial attention on the processing of congruent audiovisual speech stimuli (here indexing MI). Subjects were presented with two simultaneous visual streams (speaking lips in the left and right visual hemifields) plus a single central audio stream (spoken words). In the selective attention conditions, the auditory stream was congruent with one of the two visual streams. Subjects attended to either the congruent or the incongruent visual stream, allowing the comparison of brain activity for attended vs. unattended MI while the amount of multisensory information in the environment and the overall attentional requirements were held constant. Meridian mapping and a lateralized ‘speaking‐lips’ localizer were used to identify early visual areas and to localize regions responding to contralateral visual stimulations. Results showed that attention to the congruent audiovisual stimulus resulted in increased activation in the superior temporal sulcus, striate and extrastriate retinotopic visual cortex, and superior colliculus. These findings demonstrate that audiovisual integration and spatial attention jointly interact to influence activity in an extensive network of brain areas, including associative regions, early sensory‐specific visual cortex and subcortical structures that together contribute to the perception of a fused audiovisual percept.